1988
DOI: 10.1007/bf00332491
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thiamine and ascorbic acid supplementation on the antidotal efficacy of thiol chelators in experimental lead intoxication

Abstract: The influence of the administration of thiamine (vitamin B1), ascorbic acid (vitamin C) or their combination on the efficacy of two thiol metal chelators, viz. alpha-mercapto-beta-(2-furyl) acrylic acid (MFA) and 2,3-dimercaptosuccinic acid (DMS), in counteracting lead (Pb) toxicity was investigated in rats. Ascorbic acid or its combination with thiamine enhanced the urinary elimination of Pb, reduced the hepatic and renal burden of Pb, and reversed the Pb-induced inhibition of the activity of blood delta-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
2

Year Published

1989
1989
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 20 publications
3
25
2
Order By: Relevance
“…5). In agreement with the studies of Goyer and Cherain (4) and Dhawan et al (5), no net decrease in brain lead was observed after 5 days. Goldstein and colleagues (23) earlier found that the uptake and retention of lead by brain in immature rats was greater than in their mothers and that brain lead was not affected by EDTA.…”
Section: Recent Experimental Studiessupporting
confidence: 82%
See 1 more Smart Citation
“…5). In agreement with the studies of Goyer and Cherain (4) and Dhawan et al (5), no net decrease in brain lead was observed after 5 days. Goldstein and colleagues (23) earlier found that the uptake and retention of lead by brain in immature rats was greater than in their mothers and that brain lead was not affected by EDTA.…”
Section: Recent Experimental Studiessupporting
confidence: 82%
“…These studies were carried out on an in-patient basis to preclude the possibility of excessive ingestion of lead that might occur on an out-patient basis.' During the first 5 days, all received 1050 mg DMSA/m2/day in three divided doses. During the second five days, dosage was reduced to 350 mg DMSA/m2 day given in divided dose.…”
Section: Cana2edta: Human Studiesmentioning
confidence: 99%
“…It acts mainly as an antioxidant molecule and its beneficial effects could be attributed to its ability to complex with lead 165,166) . Animal studies have suggested an antagonistic effect of ascorbic acid on lead absorption and toxicity and ascorbic acid may even chelate lead as effectively as EDTA 154) , but studies on humans have shown some mixed results. In a study with 78 male workers, 38 received vitamin C and 38 were given a placebo 167) .…”
Section: Vitamin C (Ascorbic Acid)mentioning
confidence: 99%
“…Various vitamins have been found to reduce the toxic manifestation of lead 154) . Dietary oral supplementation with these vitamins often lessens the severity of lead poisoning by inhibiting the lead absorption or interaction at the macromolecular site of physiological action 166,171,182) .…”
Section: Vitamin E (α α α α α-Tocopherol)mentioning
confidence: 99%
“…The changes observed in the tissue metal concentrations of Tilapia florida after acute administration of the chelating agents points to the best efficacy of thiamin. Dhawan et al, (2015) observed that thiamin did not cause any major reduction in body metal content, but a combination of thiamin and ascorbic acid improved the ability of animals to excrete metals, thereby reducing the body metal content. Similarly, Bratton et al, (1981) found that thiamin had no effect on the trace metal content of plasma in cattle.…”
Section: Discussionmentioning
confidence: 93%